Anti-diabetic and anti-hyperlipidemic effects of sea cucumber (Cucumaria frondosa) gonad hydrolysates in type II diabetic rats - Tingting Wang; Lin Zheng; Shuguang Wang; Mouming Zhao; Xiaoling Liu (Food Science and Human Wellness)
The present study investigated the anti-diabetic activity and potential mechanisms of sea cucumber gonad hydrolysates (SCGH) in a rat model of type II diabetes induced by streptozotocin (STZ) combined with high-fat diet (HFD). Results showed that SCGH significantly reduced water intake, fasting blood glucose level and glycated hemoglobin level. Moreover, the oral glucose tolerance, insulin resistance and plasma lipid level in diabetic rats were also alleviated. Furthermore, histological analysis showed that SCGH effectively protected the tissue structure of liver. In addition, mechanism studies showed that SCGH improved glucose metabolism via activating the IRS/Akt signaling pathway, and promoted lipid metabolism via activating the AMPK signaling pathway. In summary, these findings suggested that SCGH have potential anti-diabetic effects by improving insulin resistance and lipid metabolism disorders.